Insects associated with chromatic traps in six lettuce cultivar (Lactuca sativa) with organic management in an agricultural orchard of the Peruvian coast - Gutiérrez-Bustamante, Silvia (2023)
Lettuce (Lactuca sativa L.) is a vegetable that presents versatility in cultivation techniques. Currently, research related to the productive behavior of cultivars and the evaluation of pests and diseases are being conducted. To minimize the damage of phytophagous insects on the production of leafy vegetables, the use of sticky traps of different colors has been recommended. Therefore, the purpose of this work was to identify the insects associated with the lettuce (L. sativa) crop trapped based on the chromatic trap (yellow and blue), using Razecol 100® (agricultural adherent), during the period from September to October 2022, under the Vegetable Research and Social Projection Program of the Universidad Nacional Agraria La Molina, Lima, Peru. 866 individuals distributed in six orders (Diptera, Hemiptera, Lepidoptera, Coleoptera, Neuroptera and Hymenoptera) and nine families were collected. The beneficial predatory fly of the genus Condylostylus sp. (Diptera: Dolichopodidae), was dominant, with 314 specimens, and was also the most abundant in the vegetable production ecosystem. In four of the five temporary sampling units, specimens of the genus Agapostemon sp. (Hymenoptera: Halictidae) and the blue color was preferred by this genus. The efficiency of yellow and blue traps in the control of pests associated with lettuce was demonstrated.